2007
DOI: 10.2337/db06-1504
|View full text |Cite|
|
Sign up to set email alerts
|

Two Years of Treatment With Dehydroepiandrosterone Does Not Improve Insulin Secretion, Insulin Action, or Postprandial Glucose Turnover in Elderly Men or Women

Abstract: To determine if dehydroepiandrosterone (DHEA) replacement improves insulin secretion, insulin action, and/or postprandial glucose metabolism, 112 elderly subjects with relative DHEA deficiency ingested a labeled mixed meal and underwent a frequently sampled intravenous glucose tolerance test before and after 2 years of either DHEA or placebo. Despite restoring DHEA sulphate concentrations to values observed in young men and women, the changes over time in fasting and postprandial glucose concentrations, meal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 52 publications
1
38
2
1
Order By: Relevance
“…We also observed that DHEA replacement did not alter net insulin action measured with the unlabeled meal minimal model (21). To our knowledge, the effects of testosterone replacement on insulin secretion, insulin action, and postprandial glucose turnover have not been previously evaluated in elderly men.…”
mentioning
confidence: 58%
“…We also observed that DHEA replacement did not alter net insulin action measured with the unlabeled meal minimal model (21). To our knowledge, the effects of testosterone replacement on insulin secretion, insulin action, and postprandial glucose turnover have not been previously evaluated in elderly men.…”
mentioning
confidence: 58%
“…18 In another study, a two-week intake of DHEA by type 2 diabetic men improved glucose control and HOMA-IR. 19 Other results however have shown that a two year intake of DHEA had no effect on insulin sensitivity 3,20 and quality of life. 20 In a study by Yamauchi et al, it was found that in diabetic men DHEA levels were significantly lower compared to men with IGT but DHEA levels were not related to insulin levels.…”
Section: Discussionmentioning
confidence: 91%
“…19 Other results however have shown that a two year intake of DHEA had no effect on insulin sensitivity 3,20 and quality of life. 20 In a study by Yamauchi et al, it was found that in diabetic men DHEA levels were significantly lower compared to men with IGT but DHEA levels were not related to insulin levels. 21 Analogous results were found by Jedrzejuk et al who studied the effect of DHEA intake for three months and found that this treatment had no effect on cholesterol, triglyceride and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 91%
“…The few studies that have addressed this issue suggest that DHEA has no effect on the metabolism of carbohydrates (B). 25 …”
Section: Recommendationmentioning
confidence: 99%
“…36 The beneficial effects of ART on metabolic syndrome components appear to be specific to testosterone, given that chronic replacement with DHEA does not improve the secretion or action of insulin and postprandial glycemia in women and elderly men (B). 40 …”
Section: Recommendationmentioning
confidence: 99%